2019
DOI: 10.1103/physreva.99.022310
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement negativity of fermions: Monotonicity, separability criterion, and classification of few-mode states

Abstract: We study quantum information aspects of the fermionic entanglement negativity recently introduced in [Phys. Rev. B 95, 165101 (2017)] based on the fermionic partial transpose. In particular, we show that it is an entanglement monotone under the action of local quantum operations and classical communications-which preserves the local fermion-number parity-and satisfies other common properties expected for an entanglement measure of mixed states. We present fermionic analogs of tripartite entangled states such a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 117 publications
(205 reference statements)
1
112
0
Order By: Relevance
“…For a system of two fermionic site, we provide an explanation based on the modified separability criterion for fermionic density matrices. We expect (but not argue) that the absence of sudden death carries through all fermionic systems with generic hopping terms [78]. A rigorous proof of the absence of sudden death in the entanglement negativity of a generic extended fermionic system with many sites or a counter example in which sudden death is observed could in principle be very enlightening.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For a system of two fermionic site, we provide an explanation based on the modified separability criterion for fermionic density matrices. We expect (but not argue) that the absence of sudden death carries through all fermionic systems with generic hopping terms [78]. A rigorous proof of the absence of sudden death in the entanglement negativity of a generic extended fermionic system with many sites or a counter example in which sudden death is observed could in principle be very enlightening.…”
Section: Discussionmentioning
confidence: 88%
“…In Refs. [66] and [78], we have shown that these issues do not carry over to our definition of partial transpose.…”
Section: Introductionmentioning
confidence: 84%
“…This is not possible for free-fermion models [80][81][82][83][84][85][86][87]. An alternative entanglement measure, which is effectively calculable using free-fermion techniques, has been introduced [15,85,86,[88][89][90], and it is also an upper bound for the negativity [87]. Very recently, much attention has been focused to study the behaviour of the negativity at a finite-temperature phase transition.…”
Section: Entanglement Entropies Mutual Information and Logarithmicmentioning
confidence: 99%
“…The finite fermionic concurrence of the reduced state ρ pq warrants non-zero bipartite entanglement for any bipartition of the four dimensional sp space [35]. In particular, ρ pq will lead to a finite up-down entanglement, which can be quantified through the pertinent negativity [39,67,68]. This partition involves four distinct states at each side: |0 , c † p− c † q− |0 , c † p− |0 and c † q− |0 for Alice and similar states at the upper level for Bob (Fig.…”
Section: Fermionic Concurrence and Reduced Up-down Entanglementmentioning
confidence: 99%
“…2), leading to a two-qudit system with d = 4. P z symmetry implies that just states with the same local fermion number parity are connected in ρ pq , entailing that partial trasposition will not mix local states with different number parity and standard formulas can be applied [39]. The ensuing negativity is just minus the sum of the two negative eigenvalues of the partial trasposed matrix:…”
Section: Fermionic Concurrence and Reduced Up-down Entanglementmentioning
confidence: 99%